Beyond joints: the importance of animal models in exploring rheumatoid arthritis comorbidities - Marco-Bonilla, Miguel; Fresnadillo, Maria; Riva-Bueno, Macarena de la; Herrero-Beaumont, Gabriel; González-Gay, Miguel Angel; Largo, Raquel; Mediero, Aránzazu (Frontiers in Medicine, 2025)
Joint inflammation is the most prominent feature of rheumatoid arthritis (RA), but this disease can affect practically any organ of the body. The association between RA and comorbidities is multifaceted, involving traditional risk factors, chronic inflammation, and the effects of medications. A large number of animal models have been developed for the study of RA. All of them developed histopathological changes, such as human diseases, and often experienced other comorbidities. The choice of one model or another depends on several factors. It is important to bear in mind, for example, the study of pathophysiological mechanisms, the progression, and the activated autoimmunity, among others. It is also necessary to know what comorbidities are described in each model, as the selection may depend on the possibility of replicating these comorbidities. In this review, we will focus on the study of cardiovascular, musculoskeletal, and hepatic comorbidities in the four most used and induced RA models: collagen-induced arthritis (CIA), adjuvant-induced arthritis (AIA), pristane-induced arthritis (PIA), and serum transfer K/BxN. In this manuscript we offer guidance on how these models replicate RA key comorbidities and how to choose the most suitable RA model.